Embracing diversity: attitudes, school climate and self-efficacy for inclusive education among international school teachers in Selangor - Yee, Tan Fang; Ahmad, Nor Aniza (Human Resource Management Academic Research Society, 2022)
One of the focuses of National Education Blueprint (2013-2025) is to improve the national policies and practices towards special education (GOM, 2013a; MOE, 2013). Numerous researches were being conducted to investigate the effectiveness, quality as well as key elements of the implementation of Inclusive Education (IE). The research design of quantitative, correlational and cross-sectional were selected to collect, measure and analyse data for (a) teacher’s level of self-efficacy, (b) teacher’s attitude as well as (c) School Climate towards IE. Besides that, this research also gathered information: (a) demographic information, (b) self-evaluation and (c) opinion towards the IE programme from the targeted sample. Approximately 280 International School Teachers were recruited to participate in this research. The data were collected, filtered and screened with Exploratory Data Analysis (EDA). The data of this research is normally distributed as the skewness value and kurtosis value fall within the range of normal distribution. Pearson Product-Moment Correlation Coefficient analysis was performed to analyse the relationship between attitudes and School Climate towards self-efficacy for IE among International School Teachers in Selangor, Malaysia. The findings of this research reported: (a) positive relationship and (b) significant relationship between teachers' attitudes, School Climate as well as teacher’s self-efficacy. However, the strengths of relationships between the variables were low. The empirical findings obtained from this research can be beneficial for educational authorities such as: (a) Ministry of Education (MOE), (b) School Administrators, (c) parents in the society of International School in Malaysia. There is limited research conducted in the setting of International Schools. Therefore, the findings can help the researchers to understand International School Teachers’ attitudes, School Climate towards Self-efficacy for IE. Further research should consider in: (a) employing qualitative research to understand the causal effect between the variables, (b) conducting interview to obtain in-depth understanding on the responses generated from questionnaire, as well as (c) expanding the targeted sample to government as well as private school teachers.